School mathematics in the chair mathematician logic elements in education from logical tests use - Ummatova Makhbubakhan Akhmedovna; Turdimatova O‘g‘iloy Muzammadali qizi (Researchparks Publishing, 2023)
This in the article mathematician logic m bees solve for necessary was knowledge , rule, proof , law , theorem , definition , hypotheses analysis done Makes sense thinking of processes stages and makes sense from the tests samples given . Study in the process student to students makes sense thought to keep regularly by teaching to go them independent , free to think , search , har one to the matter creative approach , responsibility sense , scientific research their work take go , analyze do , scientific from the literature fruitful to use has been interests strengthen based on